2019
DOI: 10.1016/j.jshs.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Heat dissipating upper body compression garment: Thermoregulatory, cardiovascular, and perceptual responses

Abstract: PurposeThe aim of the present study was to determine the effects of an upper body compression garment (UBCG) on thermoregulatory responses during cycling in a controlled laboratory thermoneutral environment (~23°C). A secondary aim was to determine the cardiovascular and perceptual responses when wearing the garment.MethodsSixteen untrained participants (age: 21.3 ± 5.7 years; peak oxygen consumption (VO2peak): 50.88 ± 8.00 mL/min/kg; mean ± SD) performed 2 cycling trials in a thermoneutral environment (~23°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 30 publications
0
22
1
Order By: Relevance
“…A small number of studies investigated other blood markers including glucose [64,89,93,119,120], blood pH [15,22,50,87,164,171], oxygen saturation of haemoglobin [12,15,50,93,167], and partial pressure of oxygen [12,15,50], with no effect of compression reported, with the exception of a positive effect in one study measuring oxygen saturation of haemoglobin [167]. For markers of coagulation and fibrinolysis two studies reported no effect [122,169], and one study [170] reported a positive effect on thrombin-antithrombin complex and plasminogen activator inhibitor with compression.…”
Section: Blood and Salivary Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…A small number of studies investigated other blood markers including glucose [64,89,93,119,120], blood pH [15,22,50,87,164,171], oxygen saturation of haemoglobin [12,15,50,93,167], and partial pressure of oxygen [12,15,50], with no effect of compression reported, with the exception of a positive effect in one study measuring oxygen saturation of haemoglobin [167]. For markers of coagulation and fibrinolysis two studies reported no effect [122,169], and one study [170] reported a positive effect on thrombin-antithrombin complex and plasminogen activator inhibitor with compression.…”
Section: Blood and Salivary Outcomesmentioning
confidence: 99%
“…Future research should aim to identify the influence of when compression is applied (during or post-exercise), and the duration of use on blood and salivary markers. In addition, further research that investigates the effects of compression on markers of coagulation and fibrinolysis during travel in athletes may be beneficial [171].…”
Section: Blood and Salivary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations